The role of affective touch in mental illness: a systematic review of CT fiber dysregulation in psychological disorders and the therapeutic potential of CT fiber stimulation - Papi, Martina; Decandia, Davide; Laricchiuta, Daniela; Cutuli, Debora; Buratta, Livia; Peciccia, Maurizio; Mazzeschi, Claudia (Frontiers in Psychiatry, 2025)
IntroductionOver the past few decades, research on affective touch has clarified its impact on key psychological functions essential for environmental adaptation, such as self-awareness, self-other differentiation, attachment, and stress response. These effects are primarily driven by the stimulation of C-tactile (CT) fibers. Despite significant advancements in understanding the fundamental mechanisms of affective touch, its clinical applications in mental health remain underdeveloped. This systematic review aims to rigorously assess the scientific literature on the relationship between CT fiber stimulation and psychological disorders, evaluating its potential as a therapeutic intervention.MethodsThis systematic review was conducted in accordance with PRISMA guidelines. A search was performed in the EMBASE, PubMed, and Web of Science databases for articles published in the last 10 years. The review focused on two main aspects: (1) potential dysregulation of CT fibers in individuals with psychological disorders, and (2) psychological treatments based on CT fiber stimulation and their psychological and functional outcomes. ResultsMost studies investigating CT fiber dysregulation in psychological disorders reported sensory alterations, with patients rating affective touch as less pleasant than healthy controls. These differences were often associated with dysregulation in the reward network and interoceptive processing, with several studies suggesting reduced insular cortex activation as a contributing factor. Regarding psychological treatments, only a limited number of studies analyzed therapies based on CT fiber stimulation. Despite methodological variations and differences in psychological diagnoses, the available evidence suggests that affective touch therapies can effectively reduce symptom severity and improve interoception across different psychological conditions.DiscussionThe findings underscore the potential of affective touch as a therapeutic avenue for psychological disorders. However, given the dearth of studies on this topic, further analyses are necessary to fully understand its mechanisms and clinical efficacy. Expanding research in this area could provide valuable insights into functional impairments related to CT fiber dysregulation and support the development of targeted interventions for mental health treatment.